2019
DOI: 10.1080/19440049.2019.1585581
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in coastal areas and seafood: implications for food safety

Abstract: Microplastics have become ubiquitous in the marine environment. Microplastics have been detected in many coastal environments and species, including commercial seafood. This triggers concern about potential economic impacts and the risks of dietary exposure, especially for coastal communities. However, data regarding the levels of microplastics in coastal seafood and their toxicological effects are still limited. Accordingly, the dietary risk is still poorly explored. This review summarizes and discusses recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
106
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(116 citation statements)
references
References 170 publications
3
106
0
7
Order By: Relevance
“…Many studies have shown that marine dietary components can play a significant role in maintaining and promoting human health (Dong et al 2019). Moreover, as an environmental issue, microplastics have attracted extensive attention for their effect on health and the harm to intestinal bacteria, hence, their accumulation in the marine environment cannot be ignored (Agamuthu et al 2019;Hantoro et al 2019;Henry et al 2019). This section summarizes the interaction between intestinal floras and dietary marine ingredients.…”
Section: Intestinal Flora and Dietary Marine Ingredientsmentioning
confidence: 99%
“…Many studies have shown that marine dietary components can play a significant role in maintaining and promoting human health (Dong et al 2019). Moreover, as an environmental issue, microplastics have attracted extensive attention for their effect on health and the harm to intestinal bacteria, hence, their accumulation in the marine environment cannot be ignored (Agamuthu et al 2019;Hantoro et al 2019;Henry et al 2019). This section summarizes the interaction between intestinal floras and dietary marine ingredients.…”
Section: Intestinal Flora and Dietary Marine Ingredientsmentioning
confidence: 99%
“…While spatial distribution of microplastics in the environment is highly complex, areas with high human population, coastal recreation, and tourism pressures generally yield high environmental microplastics (Barnes et al 2009;Hantoro et al 2019). Microplastics represent a diverse set of contaminants which encompass infinite combinations of plastic densities, sizes, shapes, surface textures, and chemical properties (Rochman et al 2019).…”
mentioning
confidence: 99%
“…While human presence may correlate with microplastic prevalence, it is unclear what specific environmental processes best predict fate and transport of these pernicious particles (Jambeck et al 2015;Zhang 2017). Density has been thought to ultimately determine environmental fate, with denser plastics like polyvinyl chloride and polyethylene terephthalate (PET) settling to the benthos and low density polymers such as polystyrene, polypropylene, and polyethylene remaining in surface waters; however, a recent review of global surface water and sediment data indicates a mixture of high and low density microplastics in water and sediment samples, attributed to influences of varied environmental and biological processes in coastal areas (Hantoro et al 2019).…”
mentioning
confidence: 99%
See 2 more Smart Citations